Pengaruh Kompres Hangat Serai dan Jahe Terhadap Penurunan Skala Nyeri Punggung Bawah Pada Nelayan - Salisatullutfiah; I Ketut Andika Priastana; I Made Rio Dwijayanto (Indonesian Journal of Health Research, 2022)
Introduction. Low back pain is pain that is felt in the lower back. Low back pain is often found in workers due to poor body position while working, such as sitting, standing or bending over for a long time. Management of low back pain can be done in a non-pharmacological way, namely by doing warm compresses of lemongrass and ginger. The purpose of this study was to analyze the effect of lemongrass and ginger warm compresses on fishermen's low back pain scale. Methods. The method used in this research is pre-experimental design with one group pretest-posttest research design. The sample of this research is 31 respondents. Measurement of pain scale using Numeric Rating Scale, pain scale is measured before and after giving compresses. Respondents were given treatment once a day for 7 consecutive days. The effect of lemongrass and ginger warm compresses on low back pain in fishermen was analyzed using the Wilcoxon Sign Rank Test. Results. The results showed that the pain scale before and after the lemongrass and ginger warm compresses showed significant results (p-value 0.000 < = 0.05), which means that there is an effect of warm lemongrass and ginger compresses on the scale of low back pain in fishermen. Conclusion. The conclusion of this study is that lemongrass and ginger warm compresses can be an alternative non-pharmacological pain management that can be used to reduce low back pain in fishermen.